Teachers’ Life Stories as a Source of Pedagogical Innovation: A Narrative Inquiry into Professional Growth - Busnawir Busnawir; Sobirin Sobirin; Eva Syafaah Hasanah; Ahmad Yani; Zain Nizam (International Journal of Educational Narratives, 2025)
Background. Teachers’ personal life stories serve as valuable sources of pedagogical reflection and innovation, providing insight into how experience shapes teaching identity and practice. Purpose. This study aims to explore how teachers’ lived experiences contribute to their professional growth and pedagogical creativity.   Method. Using a qualitative narrative inquiry approach, data were collected through in-depth interviews and reflective journals from six teachers across different educational levels. Results. The findings indicate that, regardless of proficiency level, L1, FLCA, or Thematic analysis revealed three major dimensions of professional development: (1) autobiographical reflection as a catalyst for pedagogical innovation, (2) transformation of challenges into creative teaching strategies, and (3) emotional resilience as the foundation for professional identity reconstruction. Conclusion. The study concludes that narrative-based reflection enhances teachers’ awareness of their professional journey, enabling them to reinterpret personal experiences as a source of renewal in pedagogical practices.